SAT0376 Uric Acid Levels as a Biomarker of Efficacy and Safety in Patients Treated with Pegloticase: Lessons Learned from us Clinical Experience. (23rd January 2014) - Bahrt, K.; Yeo, A.; Howson, T.; Ottery, F.
Abstract : Background: Pegloticase is a recombinant uricase recently approved in the EU for the treatment of severe, debilitating chronic tophaceous gout refractory to xanthine oxidase inhibitors (XOIs) or when XOIs are contraindicated. The pegloticase program included 2 replicate randomized, placebo-controlled trials (RCTs; 6 months; N=212) 1 followed by an open-label extension study. 2 Trial entry was preceded by a 1-week washout period for urate-lowering therapies. Patients (pts) were considered plasma uric acid (UA) "responders" if they met the primary efficacy end point of UA <6 mg/dL (360μmol/L) for 80% of time during months 3 and 6. Among pts treated with pegloticase, 42% met this end point (vs 0% with placebo; P <0.001) in the RCTs. Post-hoc analyses revealed that nonresponders to pegloticase were at increased risk for infusion reactions (IRs). Loss of response was associated with the development of high titer antibodies against pegloticase and increased drug clearance. RCT data confirmed that the majority of IRs occurred in pts who had previously lost their urate-lowering response to therapy (20/22 or 91% receiving pegloticase 8 mg q2wk and 24/34 or 71% receiving the q4wk dose). These findings led to the recommendation that pegloticase should be discontinued if UA levels rose above 6 mg/dL (particularly with 2 consecutive levels >6 mg/dL). US post-marketing pharmacovigilance data suggested that some pts were being treated concomitantly with pegloticase and XOIs. XOI use in these pts may blunt the rise of UA and invalidate UA as a biomarker of IR risk. A Dear Healthcare Provider (HCP) Letter was sent to US physicians in Dec 2011 and the US label was changed (April 2012) to recommend that oral urate-lowering medications be discontinued when pegloticase is started and not instituted during pegloticase use. Objectives: Here we report safety surveillance information on IRs, UA levels and concomitant XOI use. Methods: Post-marketing adverse events (AEs) were collected as standard, unsolicited reporting via MedWatch. All cases reported as IRs (including hypersensitivity reactions) were analyzed from Sept 14, 2010, to Sept 30, 2012, based on concomitant use of XOIs and serum UA levels at the time of the IR. Results: Reports of IRs and details of pts receiving concomitant XOIs (to be updated in 2013) are shown before and after the Dear HCP Letter (table ). Several limitations to this data should be noted: AE reporting is voluntary and may not capture all IRs, and concomitant XOI use was only recorded for those pts with reported IRs. Conclusions: Careful post-approval safety surveillance identified a potential safety concern (concomitant use of XOIs in pts treated with pegloticase). Appropriate actions (Dear HCP letter and label change) were associated with changes in physician prescribing practices. Based on AE reporting, substantially fewer pts were treated with concomitant pegloticase and XOIs after US physicians received guidance against this practice. Monitoring of UA levels prior to each pegloticase infusion—and in the absence of XOIs—remains critical to safe and effective use of pegloticase. References: Sundy et al. JAMA 2011 Becker et al. Ann Rheum Dis 2012 Disclosure of Interest: K. Bahrt Shareholder of: Savient Pharmaceuticals, Inc., Employee of: Savient Pharmaceuticals, Inc., A. Yeo Shareholder of: Savient Pharmaceuticals, Inc., Employee of: Savient Pharmaceuticals, Inc., T. Howson Shareholder of: Savient Pharmaceuticals, Inc., Employee of: Savient Pharmaceuticals, Inc., F. Ottery Shareholder of: Savient Pharmaceuticals, Inc., Employee of: Savient Pharmaceuticals, Inc.